Neglect in Older Adults: A Sociodemographic and Health Approach in the Portuguese Context - Joana Correia Jesus; Sofia von Humboldt; Luisa Soares; Isabel Leal (Social Sciences, 2024)
Southern European countries have shown indicators of accelerated aging. In Portugal, a particularly worrying aspect of this reality lies in the relationship between the aging process and the incidence of violence in older adults, as the degree of dependence and/or health status becomes a significant risk factor for the occurrence of violence. The objectives of the present study were (1) to assess the risk of violence and indicators of neglect in Portuguese older adults; (2) to examine the differences in neglect indicators according to sociodemographic characteristics and health habits. The final sample consisted of 1012 Portuguese older adults aged 65 or over. Participants were asked about sociodemographic characteristics and health habits. The risk of violence was measured using the Vulnerability to Abuse Screening Scale, and the neglect subscale of the Elder Abuse: A Multinational Prevalence Survey was used to evaluate indicators of exposure to neglect in the past year. The results show that approximately 27% of the population presents values of risk to violence. One-tenth of participants were exposed to low levels of neglect indicators and slightly fewer people (5%) were exposed to higher levels of neglect indicators. There are significant differences regarding exposure to neglect according to the age groups, gender, and marital status, depending on the living situation, years of retirement, practice of physical exercise, existence of chronic disease, alcohol consumption, and frequency of leaving home.